2007
DOI: 10.1111/j.1751-1097.2007.00203.x
|View full text |Cite
|
Sign up to set email alerts
|

Patterns in the Received Facial UV Exposure of School Children Measured at a Subtropical Latitude

Abstract: Polysulfone (PS) dosimeters have been employed to measure the erythemally effective UV exposure to the vertex, nose, cheek, chin and side facial sites of 45 volunteer high school students from Hervey Bay, Australia (25.3°S 152.9°E). The results of a series of 1 h outdoor sport trials (basketball and soccer) found the mean student facial exposure, determined as the arithmetic average of facial site exposures of unprotected students (no hat) to protected students (hat), varied from 140 ± 82 J m−2 (1σ) to 99 ± 33… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 46 publications
1
34
0
Order By: Relevance
“…Thus, the impact of sun protective behavior and changes in the built environment have been thoroughly investigated in the literature ( e.g . ). The current study demonstrated the effectiveness of an artificial shade sail in a playground, which effectively filtered out 91% of UVB 280–315 nm radiation, and reduced the SED by 60%.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…Thus, the impact of sun protective behavior and changes in the built environment have been thoroughly investigated in the literature ( e.g . ). The current study demonstrated the effectiveness of an artificial shade sail in a playground, which effectively filtered out 91% of UVB 280–315 nm radiation, and reduced the SED by 60%.…”
Section: Discussionmentioning
confidence: 89%
“…Given the potential of personal sensors to provide estimates of more representative exposures in children's populations ( e.g . ), as well as the known influence of environmental design on exposures , we assessed how stationary in situ playground UV Ery data relate to personalized UV Ery exposures of 14 children (the “human scale” of observation), with 10 subjects wearing dosimeters on each day. The 10 subjects were not present on all days, and within a day, some subjects were removed from one activity due to not feeling well, being picked up early by parents, or bathroom breaks.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Polysulfone dosimeters were used to measure the erythemally effective UV exposure to facial sites of 45 unprotected high school students (no hat) and protected students (hat), in Hervey Bay, Australia (latitude 25.3ºS). All hourly facial exposures exceeded the National Health and Medical Research Council's adopted safe daily limit of 30 J m (-2), even for those wearing hats [25].…”
Section: Discussionmentioning
confidence: 99%